PERSONAL HYGIENE BEHAVIOR RELATED TO THE INCIDENCE OF DIARRHEA IN SCHOOL-AGE CHILDREN AT BANTUL - Choirunisa, Fauziah; Hutasoit, Masta (Universitas Muhammadiyah Ponorogo, 2026)
Diarrhea is a significant health problem in children as it poses a risk of death. In Indonesia, the prevalence of diarrhea in school-aged children (6-12 years) ranges from 2-20%, with 28.9% of children affected, making it the second highest cause of death in this age group. One main contributing factor is the lack of personal hygiene behavior, which plays an important role in maintaining health, safety, and well-being. This study aimed to determine the relationship between personal hygiene behavior and the incidence of diarrhea in primary school children at SD Negeri Banguntapan Bantul. Method : Using a quantitative approach with a cross-sectional design, this study involved 77 respondents selected through total sampling and measured using a questionnaire. The Result : showed that 66.2% of respondents had poor hygiene behavior, and 75.3% experienced diarrhea. The contingency coefficient test showed a p-value of 0.000, indicating a significant relationship, with an r-value of 0.594 indicating a moderate relationship. In Conclusión : there is a significant relationship between personal hygiene behavior and the incidence of diarrhea in school-age children at SD Negeri Banguntapan Bantul.